Global change and premature hatching of aquatic embryos - Cowan, Zara‐Louise; Green, Leon; Clark, Timothy D.; Blewett, Tamzin A.; De Bonville, Jeremy; Gagnon, Thomas; Hoots, Elizabeth; Kuchenmüller, Luis; Leeuwis, Robine H. J.; Navajas Acedo, Joaquín; Rowsey, Lauren E.; Scheuffele, Hanna; et al. (Wiley-Blackwell, 2024)
Anthropogenically induced changes to the natural world are increasingly exposing organisms to stimuli and stress beyond that to which they are adapted. In aquatic systems, it is thought that certain life stages are more vulnerable than others, with embryos being flagged as highly susceptible to environmental stressors. Interestingly, evidence from across a wide range of taxa suggests that aquatic embryos can hatch prematurely, potentially as an adaptive response to external stressors, despite the potential for individual costs linked with underdeveloped behavioural and/or physiological functions. However, surprisingly little research has investigated the prevalence, causes and consequences of premature hatching, and no compilation of the literature exists. Here, we review what is known about premature hatching in aquatic embryos and discuss how this phenomenon is likely to become exacerbated with anthropogenically induced global change. Specifically, we (1) review the mechanisms of hatching, including triggers for premature hatching in experimental and natural systems; (2) discuss the potential implications of premature hatching at different levels of biological organisation from individuals to ecosystems; and (3) outline knowledge gaps and future research directions for understanding the drivers and consequences of premature hatching. We found evidence that aquatic embryos can hatch prematurely in response to a broad range of abiotic (i.e. temperature, oxygen, toxicants, light, pH, salinity) and biotic (i.e. predators, pathogens) stressors. We also provide empirical evidence that premature hatching appears to be a common response to rapid thermal ramping across fish species. We argue that premature hatching represents a fascinating yet untapped area of study, and the phenomenon may provide some additional resilience to aquatic communities in the face of ongoing global change.
Keywords: climate changes; ectotherm; embryonic development; environmental stressors; hatching mechanisms; hatching plasticity; precocious hatching